Assessing the Efficacy of Early Palliative Care Interventions on Psychological Resilience, Functional Capacity, and Health-Related Quality of Life within Patient-Caregiver Dyads in Oncology Settings - Bibi, Aneela; Abbas, Ayesha; Shahid, Omaima; Maheen, Uyaina (ACADEMIA International Journal for Social Sciences, 2025)
Cancer affects both patients and caregivers, yet the dyadic impact of early palliative care (EPC) remains underexplored. To evaluate EPC efficacy on psychological resilience, functional capacity, and health-related quality of life (HRQoL) in patient-caregiver dyads. A PRISMA-guided systematic review and meta-analysis of RCTs (PubMed, Scopus, EBSCOhost, Cochrane; to January 2024) assessing psychological, functional, and quality-of-life outcomes. Subgroup analyses compared short-term (